Patched Knockout Mouse Models of Basal Cell Carcinoma. (13th September 2012) - Nitzki, Frauke; Becker, Marco; Frommhold, Anke; Schulz-Schaeffer, Walter; Hahn, Heidi
Abstract : Basal cell carcinoma (BCC) is the most common human tumor. Mutations in the hedgehog (HH) receptor Patched (PTCH) are the main cause of BCC. Due to their high and increasing incidence, BCC are becoming all the more important for the health care system. Adequate animal models are required for the improvement of current treatment strategies. A good model should reflect the situation in humans (i.e., BCC initiation due to Ptch mutations on an immunocompetent background) and should allow for (i) BCC induction at a defined time point, (ii) analysis of defined BCC stages, and (iii) induction of BCC in 100% of animals. In addition, it should be easy to handle. Here, we compare several currently existing conventional and conditional Ptch knockout mouse models for BCC and their potential use in preclinical research. In addition, we provide new data using conditionalP t c h f l o x / f l o x mice and theK 5 - C r e - E R T + / − driver.